Collision-Induced Effects on the Dielectric Properties of Liquid Dimethylsulfoxide - Vechi Sérgio M.; Skaf Munir S. (Journal of the Brazilian Chemical Society, 2002)
We present a molecular dynamics (MD) simulation study of the dielectric properties of liquid dimethyl sulfoxide that includes interaction-induced effects due to molecular polarizability using a perturbative scheme in which the induced dipoles are computed a posteriori from the MD trajectories generated without explicit inductive forces. Static and dynamical quantities of relevance to the dielectric characterization of the liquid are reported for both polarizable and nonpolarizable versions of the system's collective dipolar densities. Our analysis within this scheme indicates that the role of the interaction induced contributions is predominantly to renormalize the magnitude of the permanent dipole fluctuations, with marginal effects upon the system's dielectric relaxation in the rotational-diffusion, microwave region of the spectrum. At higher frequencies, however, where the dielectric absorption is dominated by fast intermolecular librational motions, the dynamical effects of the molecular polarizability are more pronounced. In the presence of interaction induced contributions, the location of the peak in the MD far infrared absorption coefficient is in much better agreement with recent spectroscopic measurements of the intermolecular dynamics of this liquid.